2018
DOI: 10.1021/acs.joc.8b00593
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Synthesis of Thailanstatin A Methyl Ester and Evaluation of in Vitro Splicing Inhibition

Abstract: Thailanstatin A has been isolated recently from the fermentation broth of B. thailandensis MSMB43. We describe here an enantioselective convergent synthesis of thailanstatin A methyl ester and evaluation of its splicing activity. Synthesis of both highly functionalized tetrahydropyran rings were carried out from commercially available tri- O-acetyl-d-glucal as the key starting material. Our convergent synthesis involved the synthesis of both tetrahydropyran fragments in a highly stereoselective manner. The fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 62 publications
0
25
0
Order By: Relevance
“…Among the semisynthetic ester (40) and amide derivatives (41, 42), 40 and 41, derived from TS-A, showed higher potency in multiple cancer cell lines than their carboxylic acid precursors. [59,60] As shown in Table 2, the npropylamide 41 was two to three orders of magnitude more potent than TS-A. These data suggested that TS-A was a suitable lead compound for medicinal chemistry optimization.…”
Section: Thailanstatinsmentioning
confidence: 89%
See 1 more Smart Citation
“…Among the semisynthetic ester (40) and amide derivatives (41, 42), 40 and 41, derived from TS-A, showed higher potency in multiple cancer cell lines than their carboxylic acid precursors. [59,60] As shown in Table 2, the npropylamide 41 was two to three orders of magnitude more potent than TS-A. These data suggested that TS-A was a suitable lead compound for medicinal chemistry optimization.…”
Section: Thailanstatinsmentioning
confidence: 89%
“…The epoxide ring‐opening via halogenation modification on TS‐B and TS‐C diminished compounds’ bioactivities including anti‐proliferation and splicing inhibition, indicating the importance of C3‐epoxide for TS‐A scaffold (Table 2). Among the semisynthetic ester ( 40 ) and amide derivatives ( 41 , 42 ), 40 and 41 , derived from TS‐A, showed higher potency in multiple cancer cell lines than their carboxylic acid precursors [59,60] . As shown in Table 2, the n ‐propylamide 41 was two to three orders of magnitude more potent than TS‐A.…”
Section: Discovery and Structure‐activity Relationships Of Small‐molementioning
confidence: 99%
“…The removal of the di-tert-butylsilylene protecting group and the selective arylsulfonylation of the primary alcohol was effected with the bulky 2,4,6-triisopropylsulfonyl chloride, which upon reduction with aluminum hydride, followed by the oxidation of the remaining alcohol group gave the dihydropyran-3-one 65. In a fashion similar to that of the dihydropyranone 58 [16], the 1,4-addition of dimethyl copper lithium to 65 gave the desired cis-50 as a single diastereomer [31], allowing for a convergence with the route in Scheme 7.…”
Section: Syntheses To Generate the C-14 Stereocenter Via C-n Bond Formentioning
confidence: 94%
“…The Ghosh synthesis of spliceostatin A (4), FR901464 (1) [15,16], spliceostatin E (10) [41], and thailanstatin A methyl ester (123) [31] used the cross-metathesis strategy for the coupling of the diene 49 with 85, 115, and 102, respectively (Scheme 21). In order to avoid the decomposition problems encountered by Koide, the mixed cyclic ketal 85 was used as a coupling partner for the preparation of spliceostatin A (4).…”
Section: Fragment Coupling Via Olefin Cross-metathesismentioning
confidence: 99%
“…In the field of carbohydrate chemistry, glycoconjugates are an important class of substrates found in biologically active natural products such as papulacandin D, [1] thailanstatin A, [2] 8,10-di-O-methylbergenin, [3] vicenin-2, [4] and cassialoin. [5] The substitution of a glycosidic oxygen by a carbon atom in these molecules can significantly improve their stability towards enzymatic reactions, thus making them attractive pharmaceutical targets.…”
Section: Introductionmentioning
confidence: 99%